2011
DOI: 10.1166/jnn.2011.5102
|View full text |Cite
|
Sign up to set email alerts
|

Growth of TiO<SUB>2</SUB> with Thermal and Plasma Enhanced Atomic Layer Deposition

Abstract: We show a comparative study of the TiO2 ALD with TTIP and either O2 or O2-plasma on Si/SiO2 substrates. In particular we compare the surface morphology and crystalline phase by means of Atomic Force Microscopy (AFM), X-ray Photoelectron Spectroscopy (XPS) and X-ray Absorption Spectroscopy (XAS) for different O2-plasma procedures upon changing the time between cycles and the N2-purging pressure. The AFM images show that already these parameters may induce structural changes in the TiO2 films grown by ALD, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In order to eliminate these problems, enhancing the chemical reactivity by plasma was introduced in the ALD process. Plasmaenhanced atomic layer deposition (PEALD) has been widely used to enhance chemical reactivity between metal-organic precursors and reactant gas, reduce impurity concentrations in the films, and produce dense films [18]. However, the introduction of plasma in the ALD process can result in plasma-induced substrate and film damages by high energetic ion bombardment.…”
mentioning
confidence: 99%
“…In order to eliminate these problems, enhancing the chemical reactivity by plasma was introduced in the ALD process. Plasmaenhanced atomic layer deposition (PEALD) has been widely used to enhance chemical reactivity between metal-organic precursors and reactant gas, reduce impurity concentrations in the films, and produce dense films [18]. However, the introduction of plasma in the ALD process can result in plasma-induced substrate and film damages by high energetic ion bombardment.…”
mentioning
confidence: 99%
“…Recently, Preda et al showed for NiO/SiO 2 that in addition to the lost of long-range order, distortion at the interface induce changes in the XAS spectra [23]. It should be noticed that Ti-L 2,3 spectra with typical features of anatase and rutile TiO 2 were obtained with our ALD system when TTIP was used in connection with O 2 -plasma instead of water [17]. …”
Section: Resultsmentioning
confidence: 99%
“…1 show very small changes with increasing number of ALD cycles. Moreover, various spectral features typical of either anatase or rutile TiO 2 are absent in the XAS spectra of the ALD films [17]. These crystalline phases show a split structure for feature A; a strong and sharp peak B, and distinct pre-preak features PP.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Thin films of TiO 2 have been deposited by ALD using various precursors such as TiCl 4 , [Ti( i OPr) 4 ] (TTIP) and [Ti(NMe 2 ) 4 ] (TDMAT). [23][24][25] Additionally, heteroleptic compounds like aminoalkoxides ([Ti(NMe 2 ) 2 (dmae) 2 ]), mixed alkoxide-cyclopentadienyls ([Cp*Ti(OMe) 3 ]) and alkoxide-amidinates ([Ti(O i Pr) 3 (N i Pr-Me-amd)]) of titanium were successfully applied in ALD to grow TiO 2 thin films. [26][27][28][29] Several processes to deposit TiO 2 by thermal ALD have been described in the literature, including detailed investigations on the mechanisms and thin film characteristics.…”
Section: Introductionmentioning
confidence: 99%